CGIAR’s GDI Matrix: Promoting Transparency and Accountability for Gender, Diversity and Inclusion in CGIAR workplaces - CGIAR System Organization (CGIAR System Organization, 2020)
The GDI Matrix is a key tool to monitor and evaluate Gender, Diversity and Inclusion (GDI) in CGIAR’s Workplaces. This document describes and explains the GDI Matrix indicators. Further explanation of the GDI Matrix is provided in a separate PDF document, the GDI Matrix Factsheet.